THE EFFECTIVENESS OF A MEDICATION MONITORING CARD IN IMPROVING MEDICATION ADHERENCE AND RECOVERY AMONG ADOLESCENTS WITH TERTIAN MALARIA IN MIMIKA REGENCY, INDONESIA (Proceedings OPTIMAL, 2026)
Malaria vivax remains a communicable disease and a persistent public health problem in Mimika Regency. Non-adherence to antimalarial medication is one of the major factors contributing to disease recurrence. This study aimed to describe the effectiveness of a medication monitoring card in improving treatment adherence among adolescent patients with tertian malaria at Karang Senang Primary Health Center. A descriptive case study design was employed involving a 13-year-old adolescent diagnosed with tertian malaria. The instruments used included a malaria control card and a medication adherence monitoring sheet completed over a 14-day treatment period. Data were collected through direct observation and patient daily records and were analyzed descriptively. The results showed that the patient was able to take primaquine regularly for 14 consecutive days with a high level of adherence (SLKI score = 4.75 out of 5), although delays in medication timing occurred on three specific days. A follow-up blood examination on day 15 indicated a negative malaria result. It can be concluded that the use of a control card combined with a monitoring record is effective in improving treatment adherence and therapeutic success among adolescents with tertian malaria. It is recommended that healthcare facilities implement a simple card-based monitoring system for all malaria patients to support the national malaria elimination target by 2030.